Absorbable Synthetic Meshes in Implant-Based Breast Reconstruction After Subcutaneous Mastectomy: A Systematic Review with Clinical and Economic Considerations - Aurimas Dobilinskas; Loreta Pilipaitytė (Medicina, 2026)
Background and Objectives: Implant-based breast reconstruction following subcutaneous mastectomy is widely performed; however, the optimal strategy for implant support remains controversial. Absorbable synthetic meshes have emerged as lower-cost alternatives to acellular dermal matrix (ADM), yet their clinical and economic value remains incompletely defined. Materials and Methods: A systematic review was conducted in accordance with PRISMA guidelines using PubMed, Scopus, and Web of Science databases. Studies evaluating implant-based breast reconstruction with absorbable synthetic meshes, ADM, or without mesh were included. Outcomes of interest comprised postoperative complications, operative time, material costs, aesthetic outcomes, and patient-reported satisfaction. Methodological quality and risk of bias were assessed using design-appropriate appraisal tools. Results: Absorbable synthetic meshes were associated with low complication rates, including infection (3–8%), seroma (0–5%), hematoma (1–4%), skin necrosis (4–6%), and implant loss (3–6%). Compared with ADM, complication rates appeared comparable, while shorter operative times were reported in comparative studies. Material cost reductions of up to 90% were reported in comparative studies. Several studies reported favorable aesthetic outcomes and high patient satisfaction, although assessment methods were not standardized. Most included studies were retrospective or single-arm observational studies, with substantial clinical and methodological heterogeneity and an overall moderate risk of bias. Conclusions: Available evidence, derived predominantly from studies of polyglactin mesh, suggests that absorbable synthetic meshes may represent a feasible option for selected implant-based breast reconstructions, with potential advantages in terms of material costs and operative time. Evidence regarding polydioxanone mesh remains very limited, and the methodological limitations of the available studies preclude definitive conclusions.